Socio-Material Conflicts and Suggested Agencies for Resolution. An Anthropological Perspective of Rural Pakistan (Global Journal of Human-Social Science, 2014)
The current research was conducted to study different dimensions of social and material conflicts; it's different features, faces and also recommendations to enhance and strengthen the harmony and social management in the Village Khewaywali, (Tehsil Wazirabad) of District Gujranwala. The sample of 268 was drawn at the estimated population (876 households). A mix of anthropological tools were used to both study qualitatively and quantitatively the issues of conflicts at typical Punjabi rural community. One adult male member form every sampled household was interviewed after taking verbal communal consent. The research encompassed the reason(s) of conflict within a caste and between different castes in the village. The research proved to discover findings on both material and social conflicts in different castes of the village bisected by profession; the research also explored various socio-cultural reasons creating different material and social conflicts and recommendations to overcome disputes in an effective and efficient manner.
Keywords: conflicts; social and material conflicts; religious conflicts; kinship; caste